การเปรียบเทียบการแสดงออกของยีนในข้าว Oryza sativa L. พันธุ์เหลืองประทิว123 สายพันธุ์เดิมและสายพันธุ์ทนเค็มในภาวะเค็ม - สมพร มณีประสพสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The foliar gene expression of 2 weel-old rice (Oryza sative L.) cv. Leung Pratew 123, the original cultivar (LPT123) and the salt-tolerant line (LPT123-TC171), grown in the normal condition and treated with 0.5% (w/v) NaCI for 48 hours was compared using the differential display method. Reverse-transcription polymerase chain reaction using combination of 8 poly T oligonucleotide and 20 arbitary primers showed 108 different cDNA bands. Thirty-six CDNA fragments were cloned and sequence analysis was performed using Blast algorithm of EMBL. Twenty-seven of them were similar to the nucleotidw sequences encoding with known function proteins whereas the others showed the homology with the uncharacterized proteins. For northern blot analysis, 8 cDNA clones whose derived amino acid sequences showing the highest similarity to the rice proteins and one CDNA clone whose derived amino acid sequence was similar to protein of Klebsiella aerogenes were used as probes. Only four clones, OsD1B16-11, OsD1B15-5, OsD1B18-18 and OsD2B15-2, that had the similarity with RIM2 protein, putative 6-phosphofructo-2-kinase/ fructose-2, 6-bisphosphate 2-phosphatase hypothetical protein and NAD(P) H-quinone oxidoreductase, respectively, could hybridize with total RNA extracted from rice seedlings. The salt-stress induction of these genes was detected after 48 hours of the salt treatment. Possibly, these genes were related to salt-tolerance of the plant.